Observation on A New Diet and Significant Number of Silvery Pigeon Columba argentina on Siberut Island, Mentawai Islands, West Sumatra - Imam Taufiqurrahman; Heru Fitriadi; Aloysius Tri Antoro Widyo Utomo; Kusmiadi; Erkanus Salimu (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2026)
The Silvery Pigeon Columba argentina is one of the Greater Sundas enigmatic Columbidae. This Critically Endangered pigeon is recorded in nearly every islands offshore of west Sumatra coastline and mostly found in small flock. Its diet is poorly known, where fruits become the only dietary item ever reported. On 19 February 2026, during our survey in Siberut Island, Mentawai Islands, West Sumatra, we observed a flock of C. argentina feeding on fruits of Planchonella tree. This observation adds more fruit item into C. argentina dietary list, corroborating its frugivorous feeding status. It also highlights the importance of Siberut Island in supporting a significant population of 15 C. argentina individuals, representing approximately 6% of the global population.